The inguinal fold as a flaps bank: the inguinal fold island flap (IFI flap) - Cordova, Adriana; Rosatti, Fernando; Toia, Francesca; Di Lorenzo, Sara (Updates in Surgery, 2022)
The aim of this article is to describe an island flap, harvested from the inguinal fold, which can be used for vulvar reconstruction: the inguinal fold island flap (IFI flap). IFI flap is indicated for reconstruction of defects of vaginal vestibule and labia minora and it could be raised bilaterally safeguarding regional symmetry and avoiding vaginal introitus or urethral distortion. This flap has been utilized to reconstruct defects after vulvar melanoma and squamous cell carcinoma resections and in one case to restore vaginal vestibule anatomy in a revision surgery in a transgender woman. IFI flap is an example of an "aesthetic/functional " reconstruction which could be proposed to younger patients too.